(untitled) (Fiep Bulletin - online, 2017)
Human aging is a natural process of changes in various systems of the body. Such alterations, among other aspects, areresults of degenerative wear that diminish and limit functional capacity. Flexibility, directly related to body mobility, is one of theseaspects of functional capacity. The life expectancy of humans is now increasing. Studies indicate that lifestyle is an important aspectassociated with the aging process, and thus longevity. Adopting a healthy lifestyle of an individual can minimize or delay thedeleterious effects of aging. The practice of physical activity as one of the components of a healthy lifestyle contributes to maintainingflexibility as well as improving quality of life. The purpose of this study was to present and discuss the results of the evaluation of theflexibility of the lower and upper limbs of a group of elderly participants in SESC/Rondônia activities. A Documentary-descriptivequantitativestudy was carried out from data collected by theAssistanceProgram- TSI SESC/Rondônia. Data were collected in 2015,with 10 elderly individuals between 60 and 79 years of age, of both sexes, from the municipality of Vilhena/RO. The team followed theprotocol used in the Leisure Program Sports Physical Development/DEF andSESC / TSI program proposal. For the assessment offlexibility, the Fullerton physical fitness test was used. The same theoretical reference was used to classify the results. For statisticalanalysis, the participants were organized in groups: from 60 to 69 years; And from 70 to 79 years. The following statistical tests wereperformed: F test for variance analysis; And T test for equivalence of the means of both groups. The findings indicated that the levels offlexibility of the elderly, both lower and upper limbs are in the "Very Poor" classification, indicating a deficit in this indicator of functionalcapacity.